Hippocampal sclerosis induced in mice by a Taenia crassiceps metacestode factor. Issue 6 (23rd August 2018) - Zepeda, N.; Copitin, N.; Chávez, J.L.; García, F.; Jaimes-Miranda, F.; Rincón-Heredia, R.; Paredes, R.; Solano, S.; Fernández, A.M.; Molinari, J.L.
Abstract: An experimental Taenia crassiceps mouse model was used to assess the role of Taenia solium metacestode factor (Fac) in human neurocysticercosis. Intraperitoneal infection with T. crassiceps metacestodes or subcutaneous inoculation with a T. crassiceps metacestode factor (Fac) produced significant impairment of performance (learning) in the Barnes maze and induced bilateral hippocampal sclerosis in mice. Several staining techniques revealed important cell dispersion, extensive apoptosis and cell loss in the dentate gyrus, hilus and CA1-CA3 regions of both hippocampi, as well as intense deterioration of the adjacent cortex. An outstanding disruption of its histoarchitecture in the surrounding tissue of all these regions and apoptosis of the endothelial cells were also observed.